The motive for using Instagram social media in forming a discussion space for students - Pranata*, Randi; Widyatama, Rendra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The use of social media makes it easier for individuals in various aspects of life. This has an impact on increasing the number of social media users in Indonesia. This research aims to reveal the motives for using Instagram social media in creating a discussion space for students. Instagram, as a social media platform that is popular among students, provides space for visual interaction and conveying information through images and short text. This research examines how students use Instagram as a tool to discuss, exchange ideas, and form virtual communities in an academic environment. The research method used in this research is qualitative with a phenomenological approach. Data collection techniques were carried out through participant observation, in-depth interviews, and literature study. Survey questions focused on motivations for using Instagram for discussions, and students' perceptions of the platform's effectiveness in shaping discussion spaces. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. The results of this research show that the motives for using Instagram social media for students include the 'Because' motive and the 'For' motive. The 'Because' motives for students using Instagram are 1) Instagram social media has a very large number of users; 2) The features on Instagram are interesting to facilitate discussion; 3) Instagram makes it easier for its users with an interest algorithm system. The 'For' motif consists of 1) To convey thoughts or ideas; 2) To gain broader insight; 3)To get a relevant community.